Indolyne experimental and computational studies: synthetic applications and origins of selectivities of nucleophilic additions. - Im, G; Bronner, S; Goetz, A; Paton, R; Cheong, P; Houk, K; Garg, N (2010)
Efficient syntheses of 4,5-, 5,6-, and 6,7-indolyne precursors beginning from commercially available hydroxyindole derivatives are reported. The synthetic routes are versatile and allow access to indolyne precursors that remain unsubstituted on the pyrrole ring. Indolynes can be generated under mild fluoride-mediated conditions, trapped by a variety of nucleophilic reagents, and used to access a number of novel substituted indoles. Nucleophilic addition reactions to indolynes proceed with varying degrees of regioselectivity; distortion energies control regioselectivity and provide a simple model to predict the regioselectivity in the nucleophilic additions to indolynes and other unsymmetrical arynes. This model has led to the design of a substituted 4,5-indolyne that exhibits enhanced nucleophilic regioselectivity.